Present Status Of Medicinal and Aromatic Plants of Jammu, Kashmir and Ladakh region of Himalayas - Gangoo, S. A.; Singh, Amarjeet; Malik, A.R.; Ishtiak, Peerzada (Indian Forester, 2020)
The conservation and cultivation of medicinal and aromatic plants (MAP) are getting more importance. MAPs in India are being collected/cultivated in diverse climatic conditions starting from seacoast to high Himalayas in varied soil conditions. Among them temperate, alpine and cold arid regions of country have vital importance for MAPS. The Northern region Himalayas viz. Jammu, Kashmir and Ladakh which represents temperate, alpine and cold arid region zone finds first place in medicinal and aromatic plants conservation/cultivation. It has more than 300 MAP and out of them around 16 very important and prioritized medicinal plants viz., Aconitum heterophyllum, Artemesia absinthium, Picrorhiza kurroa, Swertia chirayita, Saussurea costus, Withania somnifera, Acorus calamus, Atropa acuminata, Berberis aristata, Cathranthus roseus, Dioscorea deltoidea, Taxus wallichiana. Podophyllum hexandrum, Hippophae rhamnoides, Dactylorhiza hatagirea and Arnebia benthamii and aromatic plants viz. Levandula officinalis, Rosmarinus officinalis, Organium vulgare. Thymus serpyllum are exclusive aromatic crops of temperate region with potential to be commercialized. Most of these plants are extracted from wild and have very high demand.